An analysis of the Research Team–Service User relationship from the Service User perspective: a consideration of 'The Three Rs' (Roles, Relations, and Responsibilities) for healthcare research organisations. (25th July 2014) - Jordan, Melanie; Rowley, Emma; Morriss, Richard; Manning, Nick
Abstract: Background: This article debates interview data from service users who engaged with the work of a Collaboration for Leadership in Applied Health Research and Care (CLAHRC). The evidence base, to date, concerning the nature of CLAHRC work at the frontline (i.e. What is it actually like to do CLAHRC work?) is meagre; thus, this article represents an original contribution to that literature. Further, this article analyses service users' participation in research – as members of the research team – and so contributes to the body of developing literature regarding involvement too. Objective: This article explores the nature of the Research Team–Service User relationship, plus associated roles, relations and responsibilities of collaborative health research. Design: Qualitative social science research was undertaken in a health‐care research organization utilizing interview method and a medical sociology and organizational sociology theoretical framework for analysis. Data utilized originate from a larger evaluation study that focuses on the CLAHRC as an iterative organization and explores members' experiences. Results: There can be a disparity between initial expectations and actual experiences of involvement for service users. Therefore, as structured via 'The Three Rs' (Roles, Relations and Responsibilities), aspects of the relationship are evaluated (e.g. motivation, altruism, satisfaction, transparency, scope, feedback, communication, time). Regarding the inclusion of service users in health research teams, a careful consideration of 'The Three Rs' is required to ensure expectations match experiences .